PENGARUH EKOSISTEM KEWIRAUSAHAAN, FAKTOR LINGKUNGAN DAN SOSIAL DENGAN DAYA SAING SEBAGAI MODERASI TERHADAP PERTUMBUHAN EKONOMI; STUDY BANDING ANTARA NEGARA MAJU DAN NEGARA BERKEMBANG - Susanti, Susanti; Mahyuddin, Mahyuddin; Syahrul Maulidi (Nusantara Hasana Journal, 2025)
This study aims to see the influence of the entrepreneurial, environmental and social ecosystems on economic growth with competitiveness variables as moderating variables, this study uses panel data of 65 countries, namely 36 developed countries and 29 developing countries, this sampling is with consideration of countries that have complete data to be studied, from 2016 to 2019. This study was conducted with three models, namely the first by looking at the influence of the entrepreneurial ecosystem on economic growth, the second model looks at its influence when moderated by competitiveness and the third model when mediated by competitiveness and finally looks at the influence of the entrepreneurial ecosystem on competitiveness. The model used is a panel data regression model, with statistical hypothesis testing and Sobel test. Empirical findings reveal that the influence of the entrepreneurial ecosystem on sustainable economic growth is greater in percentage in developed countries compared to developing countries, but conversely the influence of the entrepreneurial ecosystem on competitiveness, the presentation is lower in developed countries than developing countries. However, when competitiveness moderates between these two variables, the presentation is greater in developed countries than developing countries